Exploring the views of Malaysian hoteliers about survival during the covid-19 pandemic - Tay Kai Xin; Nur Hidayah Hamidi; Lim Le Xian (Penerbit UUM, 2024)
It is undeniable that a sudden emergence of the COVID-19 Pandemic would have certain effects on tourism, as well as the hospitality industry in Malaysia. Hence, this paper aims to closely examine the views and reactions displayed in crisis management practices pursued by hotel managers for the survival of their businesses during the pandemic. To do so, in-depth interviews were conducted, involving managers from Malaysian hotels of varying calibers (five managers from 3-star hotels, and four managers from 5-star hotels). Results showcased that certain labour actions (e.g., unpaid leave, salary cuts and layoffs) were the first and most favoured options for companies to consider in response to COVID-19. Nonetheless, this may lead to a shortage of trained staff when the hospitality industry recovers in the coming years. Another way to counter the pandemic was to rely on digital marketing and promotion to increase hotel occupancy rates during the crisis. Additionally, there were also ideas involving governmental support for the hotels during the pandemic.